Cross-sectional evaluation of perceived health care provider engagement, self-efficacy, and ART adherence in people living with HIV/AIDS. Issue 2 (1st February 2021) - Edmonds, Keith A.; Aspiras, Olivia G.; Rose, Jason P.; Gratz, Kim L.; Pinkston, Megan M.; Naifeh, James A.; Konkle-Parker, Deborah J.; Tull, Matthew T.
ABSTRACT: Despite advancements in the treatment and prevention of HIV/AIDS, adherence to antiretroviral therapy (ART) remains suboptimal. Research indicates that health care provider (HCP) engagement is related to adherence, yet little is known about the specific pathways that underlie this relation. This cross-sectional study examined the relation between perceived HCP engagement and ART adherence in people living with HIV/AIDS (PLWHA), as well as the role of adherence self-efficacy in this relation. Participants ( N  = 207) completed self-report measures assessing monthly ART adherence, perceived ability to take ART as prescribed, and perceptions of HCP engagement. Results of a path analysis revealed a direct positive relation between perceived HCP engagement and ART adherence, and a significant indirect relation of perceived HCP engagement to ART adherence through adherence self-efficacy. Higher perceived HCP engagement was related to greater adherence self-efficacy, which, in turn was related to higher ART adherence. Findings are consistent with research demonstrating that HCP support leads to increased motivation to engage in treatment and extends past work on the importance of positive patient-provider relationships. Notably, results suggest that increasing patient perceptions of HCP engagement may be one way to boost adherence self-efficacy and improve ART adherence in PLWHA.